Efektivitas Mendengarkan Murotal Al-Qur’an terhadap Derajat Insomnia pada Lansia di Selter Dongkelsari Sleman Yogyakarta - Fatma Siti Fatimah; Zulkhah Noor (Alma Ata University Press, 2015)
Merapi eruption in 2010 in Yogyakarta caused people losing their homes and triggering traumatic effect. Elderly is one of victims that vulnerable to psychological problem. The common psychological late respons due to disaster is insomnia. The impacts of insomnia are decrease the level of immunity, increase mortality and decrease quality of life, thus it needs to be solved. One of the solution is by listening murotal Al-Qur’an that will give relaxation effect. The study was aimed to know the effectiveness of listening murotal Al-Qur’an to the changing of elderly insomnia level in shelter Dongkelsari, Sleman, Yogyakarta.The design of study was a quasy experimental pre post test with control group. Technique of taking sample was probability sampling and it was found that there were 37 elderly who live in shelter Dongkelsari Sleman Yogyakarta that fulfilled the inclusion criteria. Research instrument which was used to measure insomnia level is KSPBJ questionnaire rating scale and to listen for murotal Al-Qur’an (Ar-Rahmaan) was used laptop and speaker. The duration of listening murotal Al-Qur’an was 8 days with 12 minutes for each day. Data analysis was used paired samples t test and independent samples t test. The level of insomnia for control group pre test and post test is in moderate insomnia by the mean ± SD each of them is 9.3 ± 3.7 and 10.3 ± 3.4 (p>0.05) and for intervention group there was a changing from moderate insomnia to mild insomnia by the mean ± SD each of them is 10.9 ± 3.6 and 8.2 ± 4.2 (p<0.05). There was a significant differences between the intervention group and control group by the mean ± SD each of them is -2.8 ± 3.0 and 0.9 ± 3.5 (p<0.05). In conclusion, listening murotal Al-Qur’an was effective to reduce elderly insomnia level in shelter Dongkelsari Sleman Yogyakarta.